Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.3177/jnsv.46.165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Running Exercise on Blood Pressure and Renin-Angiotensin System in Spontaneously Hypertensive Rats and Normotensive Wistar-Kyoto Rats.

Abstract: SummaryThe effect of a voluntary running exercise on blood pressure and renin-an giotensin system (RAS) was studied in male spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto rats (WKY). SHR and WKY were assigned to either voluntary running exercise or sedentary control groups at 5 wk of age. The systolic blood pressure in the exercised group for both strains of rats was significantly lower than in the sedentary control group. The plasma renin activity (PRA) and plasma renin concentration (PRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
7
1
3
Order By: Relevance
“…Surprisingly, ANG-(1-7) attenuated hypertension in 2K1C rats that were subjected to exercise swimming. Despite several studies (14,24,35) showing that exercise training caused a slight decrease in BP in hypertensive animals, we did not observe the similar result in trained 2K1C rats without ANG-(1-7) infusion. The differences may be due to the method of pressure measurement, type and duration of exercise, or animal models.…”
Section: Discussioncontrasting
confidence: 50%
“…Surprisingly, ANG-(1-7) attenuated hypertension in 2K1C rats that were subjected to exercise swimming. Despite several studies (14,24,35) showing that exercise training caused a slight decrease in BP in hypertensive animals, we did not observe the similar result in trained 2K1C rats without ANG-(1-7) infusion. The differences may be due to the method of pressure measurement, type and duration of exercise, or animal models.…”
Section: Discussioncontrasting
confidence: 50%
“…Accordingly, physical training reduced ventricular failure induced by hypertension (Moreno Júnior et al 1995), recovered ATPase activity and improved systolic function in spontaneously hypertensive rats (SHR) subjected to swimming training (Scheuer et al 1982). It has been suggested that a decreased plasma renin activity is also involved in the beneficial effects of physical training in SHR (Hayashi et al 2000;Zamo et al 2004) and in humans (Geyssant et al 1981). Furthermore, exercise training decreased plasma angiotensin (Ang) II levels in humans with chronic heart failure (Braith et al 1999).…”
mentioning
confidence: 95%
“…R bras ci Saúde 9(Sup.2):3-10, 2015 4 A hipertensão arterial (HA) é uma síndrome multifatorial caracterizada pela elevação crônica dos níveis pressóricos, sendo seu desenvolvimento dependente da interação entre predisposição genética e fatores ambientais 1 . A prevalência da HA no Brasil abrange 32,5% na população adulta, chegando a 50% nos indivíduos de 60 a 69 anos de idade.…”
unclassified
“…Além disso, a HA possui baixas taxas de controle, apesar de ser considerada um dos principais fatores de risco modificáveis das doenças cardiovasculares e um dos mais importantes problemas de saúde pública 1 . A adoção de hábitos higienodietéticos adequados, tais como a redução da massa corporal, diminuição da ingestão de sódio e gorduras, diminuição ou descontinuidade do uso de álcool e tabaco, e a prática regular de exercícios físicos, compreendem inserções não medicamentosas que diminuem o risco de desenvolvimento da HA ou dão suporte ao tratamento farmacológico, promovendo uma melhora na qualidade de vida das pessoas 2 Dentre as diferentes formas de exercício físico, o exercício aeróbico, de baixa a moderada intensidade, realizado cronicamente provoca importantes adaptações autonômicas, hemodinâmicas e humorais que influenciam positivamente o sistema cardiovascular 3 , diminuindo a atividade do sistema renina angiotensina 4 , além de reduzir o tônus simpático e melhorar a sensibilidade barorreflexa 5 . Por outro lado, apesar do treinamento resistido (TR) ser reconhecido como um importante coadjuvante nos programas de prevenção, tratamento e controle da HA 2 , algumas lacunas ainda existem à cerca dos possíveis benefícios crônicos induzidos pelo TR no controle e/ ou prevenção dessa patologia.…”
unclassified